1977
DOI: 10.1099/00221287-103-2-337
|View full text |Cite
|
Sign up to set email alerts
|

Specific Antigens of Lactobacillus acidophilus

Abstract: 337Antigens specific for Lactobacillus acidophilus were investigated by double immunodiffusion in agar-gel. Antigenic materials were extracted from whole bacteria and some walls with cold trichloroacetic acid. Antisera were prepared by intravenous injection into rabbits of suspensions of whole organisms in solutions of bovine serum albumin, which had been heated and then washed. Four specific antigens were found as precipitinogens and denoted as antigens 11, 12, 13 and 14. Of 43 strains of L. acidophilus studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Therefore, Johnson et al (28) suggested that L. acidophilus strains belonging to group A-l (17) be selected for dietary preparations on the basis of high |8-galactosidase (EC 3.2.1.23) activity, rapid acid production, growth and other desirable traits. Investigations based on agglutination tests (29), cell wall antigen (30,31), and electrophoretic and antigenic characteristics of D-and Llactate dehydrogenases (LDH) (32,33) 26) activities of this organism. Beta-galactosidase is required to sever the /3(1-4) linkage in lactose, whereas /3-fructofuranosidase is needed to sever the ß(l-2) linkage in sucrose.…”
Section: General Characteristicsmentioning
confidence: 99%
“…Therefore, Johnson et al (28) suggested that L. acidophilus strains belonging to group A-l (17) be selected for dietary preparations on the basis of high |8-galactosidase (EC 3.2.1.23) activity, rapid acid production, growth and other desirable traits. Investigations based on agglutination tests (29), cell wall antigen (30,31), and electrophoretic and antigenic characteristics of D-and Llactate dehydrogenases (LDH) (32,33) 26) activities of this organism. Beta-galactosidase is required to sever the /3(1-4) linkage in lactose, whereas /3-fructofuranosidase is needed to sever the ß(l-2) linkage in sucrose.…”
Section: General Characteristicsmentioning
confidence: 99%
“…This finding confirms the low immunogenicity of lactobacilli. 21 As both L acidophilus and T vaginalis occur in numerous serotypes,2 123 similarity of the two organisms seems to be very unlikely. Moreover, Doederlein flora comprise several species of lactobacillus, with interspecific as well as intraspecific serological differences.…”
Section: Discussionmentioning
confidence: 99%